The emotion trajectory of self-selected jazz music with lyrics: A psychophysiological perspective. (May 2022) - Warmbrodt, Ashley; Timmers, Renee; Kirk, Rory
This study explored how lyrics, participant-selected music, and emotion trajectory impact self-reported emotional (happiness, sadness, arousal, and valence) and physiological (heart, respiration, and skin conductance rates) responses. Participants were matched (based on sex, age, musicianship, and lyric preference) and assigned to a lyric or instrumental group. Each participant experienced one emotion trajectory (happy-sad or sad-happy), with alternating self- and experimenter-selected jazz music. Emotion trajectory had a significant effect on self-reports, where participants in the sad-happy trajectory reported significantly more sadness overall compared to participants in the happy-sad trajectory. There were also several interaction effects between the independent variables, which indicate the relevance of order as well as differences in processing musical emotions depending on whether music is instrumental or contains lyrics.